Alloplasmic recombinant lines (H. vulgare)-T. aestivum with 1RS.1BL translocation: initial genotypes for production of common wheat varieties - L. A. Pershina; L. I. Belova; N. V. Trubacheeva; T. S. Osadсhaya; V. K. Shumny; I. A. Belan; L. P. Rosseeva; V. V. Nemchenko; S. N. Abakumov (Вавиловский журнал генетики и селекции)
Alloplasmic lines are formed when the cytoplasm of one species is replaced by the cytoplasm of another as a result of repeated recurrent crosses of wide hybrids with the paternal genotype. Since the cytoplasm replacement results in new intergenomic interactions between a nucleus and cytoplasm leading to variability of plant characteristics, alloplasmic lines with restored fertility can be an additional source of biodiversity of cultivated plants. Earlier, recombinant alloplasmic lines (H. vulgare)-T. aestivum designated as L-17(1)–L-17(37) were formed from a plant with partially restored fertility of the BC3 generation of barley-wheat hybrid H. vulgare (cv. Nepolegayushchii) × T. aestivum (cv. Saratovskaya 29). This male-sterile hybrid was consistently backcrossed with wheat varieties Mironovskaya 808 (twice) and Saratovskaya 29, and Mironovskaya 808 had a positive impact on the restoration of fertility. This paper presents the results of investigation into a group of recombinant alloplasmic lines (L-17F4), as well as into doubled haploids (DH) lines – alloplasmic DH-17-lines obtained from anther culture of alloplasmic lines (L-17F2). The most productive of these lines were used as initial breeding genotypes. Hybrid form Lutescens 311/00-22 developed from the crossing of the alloplasmic DH(1)-17 line (as maternal genotype) with euplasmic line Com37 (CIMMYT), the source of the 1RS.1BL wheat-rye translocation, proved to be successful for breeding. The presence of the 1RS.1BL translocation in the genome of the Lutescens 311/00-22 form and the L-311(1)–L-311(6) alloplasmic lines isolated from it did not lead to a decrease of fertility or sterility in the plants. This indicates that the chromosome of the 1BS wheat does not carry the gene(s) that determine the restoration of fertility in the studied (H. vulgare)-T. aestivum alloplasmic lines. Alloplasmic lines L-311(1)–L-311(6) showed their advantage in comparison with the standard varieties for resistance to leaf and stem rust, yield, and grain quality. The breeding tests performed at Omsk Agricultural Scientific Center, Agrocomplex “Kurgansemena”, Federal State Unitary Enterprise “Ishimskoe” (Tyumen Region), using alloplasmic lines L-311(5), L-311(4) and L-311(6) resulted in varieties of spring common wheat Sigma, Uralosibirskaya 2 and Ishimskaya 11, respectively.